Neighbourhood characteristics, lifestyle factors, and child development: Secondary analysis of the All our families cohort study - MacKinnon, A. L.; Sell, H.; Silang, K.; Xie, E. B.; Jung, J. W.; Tough, S.; Tomfohr-Madsen, L. (Frontiers in Epidemiology, 2023)
Background. Neighbourhood characteristics have been found to influence child development, but little is known about lifestyle factors that may moderate this relationship, which can provide modifiable targets for policies and programing. This study investigated the association between neighbourhood characteristics (e.g., deprivation, disorder) during pregnancy and child development at age 5 in relation to various lifestyle factors (e.g., physical activity, parent-child reading, community resource use) during early childhood. Methods. A secondary analysis was conducted using multilevel modeling of data from the All Our Families cohort, recruited in Canada from 2008 to 2010. Participants self-reported on demographics during pregnancy, lifestyle factors at 3 years, and child development at 5 years using the Ages and Stages Questionnaire (ASQ-3). Neighbourhood deprivation was evaluated using the Vancouver Area Deprivation Index (VANDIX), while disorder was measured using police services’ community crime reports. Results. Geocoded information was available for 2444 participants. After adjusting for covariates, multilevel modeling indicated a significant negative association between neighbourhood deprivation and overall child development (b = -.726, 95% CI: -1.344, -.120). Parent-child reading was found to be a significant moderator of the effect of neighbourhood disorder (b = .005, 95% CI: .001, .009). There were no statistically significant moderation effects for physical activity or community resource use. Conclusion. Neighbourhood deprivation during pregnancy is associated with early child development. Parent-child reading may function as a protective factor in the presence of higher neighbourhood disorder. Overall, neighbourhood-level effects should be considered in policies and community programs that promote family and child well-being.